東ドロンイングモードランド，セール・ロンダーネ山地調査隊報告2013（JARE-55） - 菅沼, 悠介; スガヌマ, ユウスケ; 福田, 洋一; フクダ, ヨウイチ; 青山, 雄一; アオヤマ, ユウイチ; 岡田, 雅樹; オカダ, マサキ; Suganuma, Yusuke; Fukuda, Yoichi; Aoyama, Yuichi; Okada, Masaki (2014)
P(論文) 第55次日本南極地域観測隊（JARE-55）夏隊では，東ドロンイングモードランドのセール・ロンダーネ山地において絶対重力測定，無人磁力計の更新，GPSを用いた氷床流動速度の測定，およびベルジカ山地の偵察飛行を実施した．この調査はBelgian Antarctic Research Expedition（BELARE）とInternational Polar Foundation（IPF）のサポートによって実施された．本調査隊のメンバー構成は，スポット観測の測地担当2名および地形担当1名と，一般研究観測の宙空担当1名であった．南極への移動経路は往復路ともにドロンイングモードランド航空ネットワーク（DROMLAN）を利用し，空路ケープタウンから，ノボラザレフスカヤ基地滑走路を経由して現地入りした．活動地域はセール・ロンダーネ山地中部のプリンセス・エリザベス基地周辺およびシール岩（あすか基地）と，ベルジカ山地とした．本稿では観測，設営，気象をはじめとする本調査隊の行動全般について報告する． Gravity measurements, replacement of the unmanned magnetometer, and a reconnaissance flight to the Belgica Mountains were carried out in the Sør Rondane Mountains as a part of the 55 th Japanese Antarctic Research Expedition (JARE-55). The field party comprised two geodesists, one geomorphologists, and one magnetospheric scientist. The Belgian Antarctic Research Expedition (BELARE) and International Polar Foundation (IPF) supported this field expedition. Dronning Maud Land Air Network (DROMLAN) provided airborne access from Cape Town, South Africa to the Sør Rondane Mountains via Novolazarevskaya Airbase. The survey areas of this field expedition are the central parts of the Sør Rondane Mountains and the Belgica Mountains. This report summarizes the field expedition in terms of operations, logistics, and weather observations. departmental bulletin paper